"IF THE WHOLE WORLD WERE PAPER…" A HISTORY OF WRITING IN THE NORTH INDIAN VERNACULAR. Issue 4 (11th December 2018) - WILLIAMS, TYLER
ABSTRACT: The poetic and hagiographical works of early modern north Indian saints constitute a rich case study for understanding the relationship among changes in language, material practices of writing, and ideologies of writing. Beginning in the fourteenth century, the commitment of the vernacular language of bhāṣā to writing had the effect of reconfiguring practices and ideologies of writing, posing a serious challenge to the epistemic and cultural privilege formerly accorded to writing in the literary, intellectual, and religious traditions contained in Sanskrit, Persian, and Arabic. Although unable to completely escape the conceptual structures of a postliterate society, these supposedly illiterate, subaltern poet‐saints were able to undermine systems of religious and intellectual authority by questioning the ontological status and epistemic utility of written language and by divesting writing of its aura. They did so by emphasizing the materiality and banality of writing and by characterizing inscription as just another form of worldly labor. Such readings of the saints' poetic works are made possible precisely by their authorial personas as subaltern, illiterate figures, and these personas are in turn established not in the poetry itself but in the hagiographical works that narrativize these saints' lives. Importantly, these hagiographies reflect a concern with historicizing both the saints' utterances and the material processes through which those utterances came to be written down. Perhaps paradoxically, it is this concern with historicity that enables the tradition to establish the transcendent nature of the saints' speech and thought, and to enable those in the present to recreate the transformative speech acts that the hagiographies describe.